2021
DOI: 10.1002/pip.3464
|View full text |Cite
|
Sign up to set email alerts
|

24.58% efficient commercial n‐type silicon solar cells with hydrogenation

Abstract: Tunnelling oxide passivated contact (TOPCon) solar cells are gaining significant commercial interest, due to the potential for high efficiency. Industrially, this passivated contact scheme is typically coupled with an n-type Czochralski (Cz) wafer. JinkoSolar Holding Co., Ltd. is one of the leading manufacturers that are producing n-type TOPCon solar cells (referred to as 'HOT' cells) on a commercial scale. In this work, the influence of a post-cell hydrogenation step, using illumination from an LED light sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The box and whiskers correspond to the 5th, 25th, 50th (median), 75th and 95th percentile of each split 718 mV achieved for this cell architecture. 33 When comparing the iV OC -to-V OC difference in this study (Figure 5), a larger drop of 12-15 mV is observed for the 150 Ω/sq emitter compared to an 8 mV drop for the 70 Ω/sq emitter. This is due to the expected increase in J 0 metal recombination (J 0metal ) to the lowly doped regions for the 150 Ω/sq emitter.…”
Section: Oc Losses and J 0 Contributionsmentioning
confidence: 54%
“…The box and whiskers correspond to the 5th, 25th, 50th (median), 75th and 95th percentile of each split 718 mV achieved for this cell architecture. 33 When comparing the iV OC -to-V OC difference in this study (Figure 5), a larger drop of 12-15 mV is observed for the 150 Ω/sq emitter compared to an 8 mV drop for the 70 Ω/sq emitter. This is due to the expected increase in J 0 metal recombination (J 0metal ) to the lowly doped regions for the 150 Ω/sq emitter.…”
Section: Oc Losses and J 0 Contributionsmentioning
confidence: 54%
“…[ 48–50 ] The Ga 2 O 3 and Cu 2 O heterojunction is known for generating high values of V oc owing to their suitable band alignment. [ 34,35 ] Ga 2 O 3 exhibited an improved offset of the conduction band with Cu 2 O compared with those obtained when layers of other oxides were used.…”
Section: Resultsmentioning
confidence: 78%
“…Commercialized Si solar cells can provide a high power output [ 35 ] and exhibit high absorption in the IR and visible regions. However, high‐energy UV photons cause heating, discoloration, delamination, and deterioration of the passivation layer of Si solar cells, because of which their PV performance deteriorates over time.…”
Section: Resultsmentioning
confidence: 99%
“…56,57 Of these, only the combination of a thin silicon oxide coated with a heavily doped polysilicon layer has been intensely studied as a passivating contact for industrial silicon solar cells. 58,59 This passivation approach removes the need for a heavy diffusion in the following way. A tunnelling oxide on the wafer surface only allows one type of charge carrier to pass because there is a highly doped polycrystalline silicon layer behind, which pins the Fermi level to a band, which, in turn, is contacted by metal.…”
Section: Energy and Environmental Sciencementioning
confidence: 99%